(untitled) (Journal of Asian Development Studies, 2026)
This study aims to investigate the relationships among green technological innovation (GTI), renewable energy consumption (REC), and economic growth and carbon emissions in China, Russia, Brazil, and India, using panel data from 2001 to 2024. To address cross-sectional dependence and heterogeneity, a fixed-effects model with Driscoll-Kraay standard errors is employed. The findings show that renewable energy consumption significantly reduces carbon emissions in these economies, while GTI, economic growth, and trade openness are positively linked with CO2 emissions. Thus, the outcomes show that current technological innovations may still be closely connected to carbon-intensive industrial activities. These outcomes suggest that increasing the adoption of renewable energy sources and shifting innovation priorities toward clean technologies are essential to support sustainable development and achieve significant reductions in carbon emissions in emergingeconomies.